Transformation of Islamic Education at Ma'had Aly Situbondo as a Producer of Scholars Experts in Usul Fiqh (1990-2045) - Abdurahman, Abdurahman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the evolution of Ma'had Aly Situbondo and its alignment with Indonesia’s Vision 2045, emphasizing the institution’s potential contribution to globally competitive Islamic higher education. The main objective of this research is to demonstrate that the educational approach implemented at Ma'had Aly is capable of engaging with international academic standards, while also identifying strategic transformations undertaken to shape future-oriented learning envisioned for 2045. Using a qualitative framework with a taxonomic design, the study collected data through non-participant triangulation to ensure depth, validity, and contextual accuracy. Data analysis employed descriptive qualitative procedures to capture historical trajectories, contemporary developments, and projected directions of institutional change. The findings indicate that Ma'had Aly Situbondo has experienced significant transformation, particularly in curriculum renewal, enhancement of scholarly productivity, and the strengthening of scientific traditions within Islamic studies. Historically, Ma'had Aly has demonstrated its capacity to compete at the global level, as reflected in increasing literacy, analytical competence, and critical thinking skills among students in responding to contemporary intellectual and social challenges. These achievements suggest that Ma'had Aly possesses solid academic foundations that can support Indonesia’s broader human resource development agenda. Nevertheless, the study also identifies persistent limitations, especially in the integration of educational technology. Despite notable progress in academic culture and intellectual development, Ma'had Aly continues to face constraints related to advanced digital infrastructure, technological innovation, and data-driven learning systems. Addressing these challenges is essential for Ma'had Aly to fully realize its strategic role within the framework of Indonesia Vision 2045.